What should teachers know about technology? : perspectives and practices - Zhao, Yong, 1965- (Research methods for educational technology., 2003)
Schools and colleges of teacher education are called upon to prepare teachers to use technology. The ability to use technology has been established as a requirement for teacher licensing, certification, and sometimes employment. This book offers a comprehensive picture of the prominent perspectives on technology literacy for teachers and current practices in preparing teachers to become technologically literate. Articles included in this volume address such pressing issues as the theoretical foundations of teacher technology knowledge, the role of technology in teaching, technology standards for teachers, and effective approaches to prepare technologically competent teachers.